2018
DOI: 10.3390/molecules23050986
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, Antiproliferative and Antimicrobial Activities of Phenolic Compounds from Three Myrcia Species

Abstract: Myrcia bella Cambess., Myrcia fallax (Rich.) DC. and Myrcia guianensis (Aubl.) DC. (Myrtaceae) are trees found in Brazilian Cerrado. They have been widely used in folk medicine for the treatment of gastrointestinal disorders, hemorrhagic and infectious diseases. Few reports have been found in the literature connecting their phenolic composition and biological activities. In this regard, we have profiled the main phenolic constituents of Myrcia spp. leaves extracts by ESI(−)Q-TOF-MS. The main constituents found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…It should be mentioned that previous bioactivity studies [2][3][4]6] have indicated that specific flavonoids are most likely involved in the medicinal properties of M. bella extracts. In particular, antidiabetic [4] and antimutagenic [2] activities were correlated with the presence of flavonoids, while antimicrobial [3] activity has been associated with the presence of hydrolyzable tannins. The existence of three distinct chemotypes revealed in this study could play a role in the pharmacological effects of the extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that previous bioactivity studies [2][3][4]6] have indicated that specific flavonoids are most likely involved in the medicinal properties of M. bella extracts. In particular, antidiabetic [4] and antimutagenic [2] activities were correlated with the presence of flavonoids, while antimicrobial [3] activity has been associated with the presence of hydrolyzable tannins. The existence of three distinct chemotypes revealed in this study could play a role in the pharmacological effects of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, phenolic compounds were related to bioactivity. Phytochemical studies of the leaves of M. bella have described several derivatives of O-glycoside flavonols and phenolic acids [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely dispersed in the Americas and in Australia, although it is found all over the world [2]. In Brazil, there are 23 genera and approximately 1034 species present throughout the country [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is maintained in the tumour microenvironment to sustain cancer progression [18]. So, redox regulation seems to be the key factor in regulating carcinogenesis and may be modulated by phenolic antioxidants, as commonly found in Myrtaceae [18] [19],. Moreover, chemotherapeutic drugs can cause serious side effects and drug resistance, which pose limiting factors in the long-term use of these drugs.…”
Section: Introductionmentioning
confidence: 99%